CRIMES OF ILLEGAL CONNECTIONS TO ELECTRICAL NETWORKS FOR COMMERCIAL PURPOSES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
On the basis of national legislation, we will get acquainted with the principles of responsibility for the theft of electric energy and the procedure for regulation by which laws and the reforms that are being carried out on the development of these laws.